2021
DOI: 10.3390/molecules26103018
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the CYP3A4 Enzyme Inhibition Potential of Selected Flavonoids

Abstract: Acacetin, apigenin, chrysin, and pinocembrin are flavonoid aglycones found in foods such as parsley, honey, celery, and chamomile tea. Flavonoids can act as substrates and inhibitors of the CYP3A4 enzyme, a heme containing enzyme responsible for the metabolism of one third of drugs on the market. The aim of this study was to investigate the inhibitory effect of selected flavonoids on the CYP3A4 enzyme, the kinetics of inhibition, the possible covalent binding of the inhibitor to the enzyme, and whether flavono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 42 publications
(50 reference statements)
1
10
0
Order By: Relevance
“…Flavonoids and their glycosides are the most predominant class in A. judaica L. They are represented by quercetin, rutin, apigenin, rhoifolin, vitexin, kaempferol, fisetin, orientin, luteolin, isorhamnetin, naringenin, diosmetin, and acacetin. The therapeutic potential of these flavonoids has been described as antioxidant, neuroprotective, anti-mutagenic, anti-cancer, and anti-inflammatory agents [ 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 ]. Their anti-cancer activity is related to their ability to induce apoptosis and inhibit the angiogenesis process [ 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…Flavonoids and their glycosides are the most predominant class in A. judaica L. They are represented by quercetin, rutin, apigenin, rhoifolin, vitexin, kaempferol, fisetin, orientin, luteolin, isorhamnetin, naringenin, diosmetin, and acacetin. The therapeutic potential of these flavonoids has been described as antioxidant, neuroprotective, anti-mutagenic, anti-cancer, and anti-inflammatory agents [ 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 ]. Their anti-cancer activity is related to their ability to induce apoptosis and inhibit the angiogenesis process [ 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous clinical and pre-clinical experimental studies have demonstrated the good pharmacokinetic profile of Pin, which is highlighted by its rapid absorption and wide distribution with negligible residue accumulation ( 94 , 98 , 99 ). In the context of Dox, Pin being a known inhibitor of CYP3A4 and also being implicated in the inhibition of CYP2D6, suggests that co-administering Dox with Pin might give rise to herb-drug interactions ( 100 ). Depending on how potently Pin inhibits CYP2D6, in comparison to Dox, may either increase the bioavailability of Dox plasma concentration or reduce it.…”
Section: Dic: Are Today's Cancer Survivors the Future Cvd Patientsmentioning
confidence: 99%
“…These type of inhibitions are based on the inactivation of the CYP enzyme via metabolic intermediates that bind reversibly or irreversibly to the enzyme. The clinical implications of the irreversible inhibition are expected to last longer than those of the reversible inhibitor after multiple treatment doses ( 100 ). This enables clinicians to plan for the appropriate scheduling of sequential regimens that either both inhibit or induce CYP2D6 and CYP3A4.…”
Section: Dic: Are Today's Cancer Survivors the Future Cvd Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…The regulating effects of the key compounds, which included naringenin, tangeretin, nobiletin, and apigenin, on UGT1A1 and CYP3A4 were also preliminarily observed in vitro. In fact, some recent studies focused on the capability of the compounds to regulate the drug-metabolizing enzymes, although the action tendency might be reversed due to different experimental systems and conditions. As widely known, CYP450 played a pivotal role in drug metabolism, since the majority of hepatically cleared drugs depended on CYP450 for metabolism . GF inhibited intestinal and hepatic CYP3A4 in an exposure-dependent fashion, and patients taking CYP3A4 substrates are at risk of developing drug-related adverse events if consuming large amounts of GF .…”
Section: Discussionmentioning
confidence: 99%